Proceedings of the 9th International Modal Analysis Conference, April 15-18, 1991, Firenze Incontra, Centro Affari, Florence, Italy - International Modal Analysis Conference (9th : 1991 : Florence, Italy); Union College. Graduate and Continuing Studies; Society for Experimental Mechanics (Schenectady, NY : Union College, 1991)
09